Varietal Identification of Cereal Grains: Review - Deore, Anagha; Athmaselvi, K.A. (Current Nutrition & Food Science, 2024)
Large numbers of grain varieties are exploited for different purposes and their characteristics contribute in varied manners to the type, quality of the product. The variety of the grain is an important factor in deciding the value of the product. Identifying these varieties and cultivars is a crucial procedure in a food supply system. Various methods are employed to identify the variety of grains based on morphological, biochemical, or genotypic characteristics of the grain. This note discusses the need for identifying the variety of grains and looks upon various methods that have been brought into action to meet the purpose. Each method of identification has its own set of benefits and drawbacks, making it possible to choose the appropriate one for cereal grains at different stages of the supply chain. The methods of identification described in the review present an alternative to conventional manual methods. Rapid detection and accuracy are expected from the identification methods. Lab-on-a-chip, web portals, and QR codes are just a few of the recent solutions that have the ability to overcome the drawbacks and make variety identification an uncomplicated job.
Keywords: cereal